Developing an interprofessional self-reflection logbook in reproductive health in low-middle income countries: educational design research - Fatikhu Yatuni Asmara; Marco Versluis; Dian Puspita Dewi; Diana Nur Afifah; Jan-Jaap Reinders; Tri Nur Kristina; Nynke Scherpbier (Korean Journal of Medical Education, 2026)
Purpose: Remoteness from institutions challenges supervision in interprofessional education (IPE) in a community setting in reproductive health in low- and middle-income countries (LMIC). In this setting, IPE would benefit from an instrument that supports self-reflection. The use of logbooks could provide such an instrument. This study aims to develop and validate a logbook as a self-reflection instrument.Methods: The authors used an Educational Design Research (EDR) approach to develop a logbook as a self-reflection instrument for an IPE on reproductive health in a community setting in Indonesia. We evaluated the IPE program and conducted a literature review (Phase 1: analysis and exploration). Based on Phase 1, we developed a logbook referred to the Gibbs Reflective Cycle and asked experts, instructors, and students to provide feedback (Phase 2: design and construction). We conducted a pilot test and evaluated the instructors’ and students’ perceptions of using the logbook (Phase 3: evaluation and reflection). The Kruskal-Wallis test was used to compare the perceptions across disciplines.Results: The logbook integrated shared decision-making into IPE competencies and enabled assessment of students’ self-reflection. Both students and instructors reported positive perceptions, with mean scores of 4.35 (standard deviation [SD]=0.41) and 4.30 (SD=0.44), respectively. No significant differences in the perceptions were found across disciplines (p=0.719 and 0.096).Conclusion: The involvement of students, instructors, and experts in an iterative process in EDR developed and validated a logbook as a self-reflection instrument in reproductive health in LMIC.